Inteligencias múltiples percibidas por las docentes de los estudiantes de cinco años de la Red 01 Región Callao - Ipanaqué Moreno, María Carmen Rosa (2012)
The aim of this study was to describe the multiple intelligences in students 5 years of educational institutions of the network 01 of Callao, measured with the scale of observation of Multiple Intelligences (Walls, 1999), in dimensions linguistic intelligence, logical mathematical , spatial, kinesthetic, musical, interpersonal and intrapersonal. The research design used was descriptive simple. As the sample 100 students from preschool 52 men, 48 women and 5 teachers. The results show that children of five are properly developed linguistic intelligence and a low development of other intelligences. Other important findings are that children manifest early on insufficient development of logical-mathematical intelligence. In the initial level curriculum is not developing efficient spatial, kinesthetic and musical areas despite being an important part of this level.